Analysis and Application of Quadratic B-spline Interpolation for Boundary Value Problems (Global Journal of Science Frontier Research, 2020)
B-splines interpolations are very popular tools for interpolating the differential equations under boundary conditions which were pioneered by Maria et.al.[16] allowing us to approximate the ordinary differential equations (ODE). The purpose of this manuscript is to analyze and test the applicability of quadratic B-spline in ODEwithdata interpolation, and the solving of boundary value problems.A numerical example has been given and the error in comparison with the exact value has been shown in tabulated form, and also graphical representations are shown. Maple soft and MATLAB 7.0 are used here to calculate the numerical results and to represent the comparative graphs.
Keywords: B-splines interpolation; polynomial; approximate solution; curve approximation